Sosialisasi dan Realisasi Hasil Pengukuran Geolistrik untuk Eksplorasi Sumber Air Tanah di Desa Metenggeng, Kecamatan Bojongsari Kabupaten Purbalingga - Muhammad Sehah (Jurnal Serambi Abdimas, 2021)
Abstract – Drought is a disaster that often occurs in Metenggeng Village, Bojongsari District, Purbalingga Regency. In order to solve this problem, the Community Service team of Jenderal Sudirman University has collaborated with the Indonesian Wells Waqf team to do geoelectric measurements to drill wells in the Al-Jihad Mosque complex. The results of geoelectrical measurements show that the aquifer layer is obtained at a depth of more than 30.72 m and a resistivity value of 15.05 m. The socialization of the results of geoelectric measurements for the exploration of groundwater sources at the Al-Jihad Mosque in Metenggeng Village has been carried out with a very good response from the target audience. The construction and handover of wells with a depth of 50 m have also been well realized. A strong supporting factor for the success of community service activities is the willingness and realization of the target audience to maintain the sustainability of the drilled well so that it can be used for the community for a long time.